Junior High School Students’ Critical Thinking in Solving Relations and Functions Problems: A Metacognitive Approach - Eka Ninda Febintatias; Mohammad Syaifuddin; Zukhrufurrohmah (Journal of Education Reseach and Evaluation, 2025)
Mathematics learning is ideally expected to foster critical and reflective thinking skills, yet international assessments such as PISA indicate that most Indonesian junior high school students remain at a basic competency level. This gap is evident in their difficulty solving problems that require analysis, evaluation, and drawing conclusions, particularly in the topic of relations and functions. This study aimed to analyze and map the critical thinking skills of junior high school students in solving relations and functions problems based on categories of metacognitive ability. A descriptive qualitative approach with instrument triangulation was employed. A total of 31 students completed a metacognitive awareness questionnaire and a critical thinking test, after which six students representing high, medium, and low categories were selected for reflective interviews. Data were thematically analyzed through cross-instrument triangulation. The findings revealed that students’ critical thinking skills did not always align with their perceived metacognitive categories; actual cognitive regulation was more decisive than declarative awareness. These findings emphasize the importance of process-based assessment that integrates tests, questionnaires, and interviews, as well as instructional practices that explicitly foster planning, monitoring, and evaluation strategies. Theoretically, this study strengthens the understanding of the interaction between metacognition and critical thinking, while practically it provides recommendations for teachers and policymakers to design learning and assessment strategies that promote cognitive regulation and address affective factors such as motivation and self-confidence.